A formação de formadores por meio dos multiletramentos em uma Diretoria de Ensino da rede pública estadual de São Paulo - Nabôas, Lizandra Quintal (2020)
The daily work of the pedagogical coordinating teacher in the school unit is permeated by countless attributions and roles that are part of his professional identity constitution built (DUBAR, 2005) not only by his continuous training, but also by his socio-historical-cultural process. The study has as general objective, to analyze, a formation of pedagogical coordinating teacher through Multiliteracies (ROJO, 2012) in a teaching directorate of the state public network. It focused on the description of training meetings held every two weeks on the premises of the teaching directorate, with the participation of 36 pedagogical coordinating teachers entering the function in the first semester of 2019, of two coordinating teachers of the pedagogical center and the researcher-trainer who was in charge of the formative meetings. The present research has as a guiding question to investigate to what extent the pedagogy of the Multiliteracies enables the discussion about the identity constitution of the pedagogical coordinating teacher. This critical paradigm work, based on the critical collaboration research developed by Magalhães (2011), is based on the intentional transformation of contexts and of all the participants involved. The research data, with a qualitative approach, were collected from the analysis of the video recording, from the minutes produced at each formative meeting and through semi-structured interviews conducted later with two coordinating pedagogical teachers. As a result, the formative meeting under the Multiliteracies Pedagogy approach contributed to the construction of the concept of Professional Identity not only for the group of incoming pedagogical coordinating teachers, but also with the formation of the researcher-trainer. He also contributed to the realization of daily actions that legitimize the role of trainer, articulator and transformative pedagogical coordinating teacher with a view to transforming the school community